1977
DOI: 10.3406/reg.1977.4155
|View full text |Cite
|
Sign up to set email alerts
|

Les temps de l'Impératif dans les ordres de l'orateur au greffier

Abstract: L'emploi constant du présent ou de l'aoriste dans les formules injonctives κάλει (τὸν δεῖνα), λαβὲ (τὴν μαρτυρίαν) et l'alternance des temps du verbe «lire» : ἀναγίγνωσκε /ἀνάγνωθι ne s'expliquent de manière satisfaisante ni par l'opposition traditionnelle entre duratif (continué) et ponctuel (inchoatif, terminal), ni par l'absence ou la présence d'une tonalité affective. Parce qu'il « ouvre une perspective sur l'action » (H. Seiler), l'impératif présent met l'accent sur son exécution et signale l'effacement d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Several Mediterranean civilizations were designated as having possibly contributed to the introduction of the common genet in Europe; yet again concrete grounds are missing. The most elaborated scenario to date, based on Cyrenaican coinage and Heredotus' description of the Lybian fauna, suggested that the species was introduced by the Greeks from their Libyan colonies (Amigues 1999). This widens the debate to a possible spread by the first great sailors of the Mediterranean, the Phoenicians, whom were initially based in the coastal Middle East (current Lebanon and Israel).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several Mediterranean civilizations were designated as having possibly contributed to the introduction of the common genet in Europe; yet again concrete grounds are missing. The most elaborated scenario to date, based on Cyrenaican coinage and Heredotus' description of the Lybian fauna, suggested that the species was introduced by the Greeks from their Libyan colonies (Amigues 1999). This widens the debate to a possible spread by the first great sailors of the Mediterranean, the Phoenicians, whom were initially based in the coastal Middle East (current Lebanon and Israel).…”
Section: Discussionmentioning
confidence: 99%
“…through rafting) earlier than 110,000-170,000 years ago, and thus was not renewed later; an unlikely hypothesis given the low support from biogeographical data in the region (Dobson 1998;Cosson et al 2005), the genetic diversity detected in Europe (lower than in northern Algeria, but not diagnostic of a strong founder event), the presence of common genets in Balearic Isl., and the genetic evidence for multiple introductions (see below). We would thus opt for recent events of introduction conditioned by cultural constraint, although this scenario still suffers from a lack of archaeozoological evidence relative to the possible use of the common genet against pests in the Mediterranean Basin (Kingdon 1977;Amigues 1999). Interestingly, an example of a culturally dependant introduction was recently reported for the Algerian hedgehog Atelerix algirus, which was introduced by the Almohads from Morocco to the Mediterranean islands and the coastal Iberian Peninsula for meat consumption and medicine (Morales and Rofes 2008).…”
Section: Translocation Scenarios and Historical Demography Of The Eurmentioning
confidence: 94%
See 2 more Smart Citations
“…The introduction of the species has traditionally been associated to the Muslim invasion of Iberia (Spain and Portugal) starting 711 A.D. (Morales 1994), although a Greek historical source suggested its presence in Europe as early as the 6th century B.C. (Amigues 1999). Recent investigations based on mitochondrial DNA (mtDNA) reassessed these views, and suggested that the species was introduced from an endemic North African lineage into Andalusia (southern Spain), Catalonia (northwestern Spain), Mallorca and Ibiza (Balearic Isl.…”
Section: Introductionmentioning
confidence: 99%